Integration of Artificial Intelligence on Teaching the Course of Didactic Methodology: A Case Study - Mavropoulou, Eleni; Koutsoukos, M.; Oikonomou, A. (European Journal of Social Science Education and Research, 2023)
The potential of artificial intelligence is exploding in various aspects of daily and working life, improving the standard of living for people worldwide. In this light, it is clear that the field of education cannot remain unaffected. New research is bringing to light the advantages and challenges of integrating artificial intelligence into education with increasing frequency. With technological advancements and new opportunities emerging, the potential applications of artificial intelligence continue to expand. In order to maximize learning outcomes and promote holistic development in students, teachers must leverage AI effectively. The purpose of this paper is to examine the use of artificial intelligence in teaching the course of Didactic Methodology as part of the pedagogical education of Secondary school teachers. Using insights from relevant studies, the study examines whether Artificial Intelligence enhances the educational process. Artificial Intelligence for educational purposes will be reviewed in terms of its advantages and challenges. In the following case study, an entire didactic lesson will be described and learning materials will be provided. As part of this project, Artificial Intelligence (AI) was asked to create learning materials for a whole lesson within the course. Based on the course needs, learning materials were collected and structured. After generating the learning material, it was analysed and studied accordingly. The evaluation of the learning material will be done in relation to the course objective and the degree to which this has been achieved will be judged by the students’ learning outcomes. As demonstrated in this study, Artificial Intelligence is able to provide satisfactory answers, and it can be used to customize teaching materials to meet the needs of teachers. This paper is intended to meet teachers’ needs as well as those of contemporary digital societies in the 21st century.